Testing the effect of including oral health in general health checks for elderly patients in medical practice – a randomized controlled trial - Lowe C, Blinkhorn AS, Worthington HV, Craven R. (Blackwell Synergy, 2007)
To test the feasibility and effectiveness of an oral health referral process for elderly patients (aged 75 years or over) attending a preventive health check (PHC) with their general medical practitioner.